Hydrology And Hydraulics Of The Lubigi Wetland In Uganda - Kayima., John, K.; Mayo., Aloyce, W.; Nobert, Joel, K. (Tanzania Journal of Engineering and Technology, 2018)
The Lubigi wetland, which is located in the north-western part of Kampala, receives polluted water from Kampala city and discharges it into Mayanja River. However, there is lack of information and knowledge on the hydrology and hydraulics of the Lubigi wetland, which are important for protection of wetland ecosystems and fulfill the Uganda national policy for the conservation and management of wetland resources. The national policy aims at promoting the conservation of Uganda ' s wetlands, in order to sustain their ecological and socio-economic functions for the present and future well- being of all the people of Uganda. Pertinent data collection, field tests and surveys were carried out to gather data necessary for establishing the current status of the hydraulics and hydrology of Lubigi wetland. The results revealed that the Lubigi wetland demonstrates considerable impounding reservoir and flood buffering capacity. This is an important service provided by the wetland, to alleviate possible negative impacts of storms and floods events. The Lubigi wetland total influents and effluents discharges, have mean values of 222,377.60 ±132,365 m3 /day and 221,356.80 ±122,256 m3 /d, respectively. The wetland water balance is dominated by the influent discharges which account for 93.21% of the total water influx, and the effluent discharges which account for 97.7% of the total water outflow. The wetland main study area hydraulic residence times, varies between 6.0 hours and 10 days. Hence, the wetland is endowed with abundant water fluxes, water impounding capacity and adequate hydraulic retention times. The volumetric efficiency of the wetland main study area is 63% and 38% during wet season and dry season, respectively. This indicates that on average only about 50% of the volume of the Lubigi wetland main study area is lost through short-circuiting. The dispersion number of the wetland was about 0.01 to 0.03, which indicates that the flow regime through wetland is close to plug flow. Key words: Lubigi wetland, Hydraulics, Hydrology